FTIR-ATR for the identification of Psidium guajava plants infested with Meloidogyne enterolobii - Casassa-Padrón, Ana; Portillo, Edgar; González, Cesar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The Meloidogyne enterolobii Yang and Eisenback nematode represents one of the most devastating pests in guava cultivation in Venezuela and the world. The diagnosis of this parasite requires specialized knowledge and very laborious procedures. The objective of this research was to identify the infrared spectra of guava plants, in the nursery phase, infested with M. enterolobii using Fourier-transform infrared spectroscopy coupled to attenuated total reflectance (FTIR-ATR). Leaves from healthy and infested plants were taken 60 days after nematode inoculation and  analyzed in a FTIR-ATR spectrometer. The main spectral bands corresponding to the chemical compounds (lipids, proteins and carbohydrates) produced by plant metabolism as a result of nematode infestation were characterized. These results represent the starting point to determine the potential of this rapid and non-destructive technique for the early diagnosis of plants infested by the “guava root-knot nematode”.